Analysis of Mode Integration Facilities at Madiun Station - Nopriyanto, Windi; Widi Astuti, Septiana; Dewi, Puspita (ASTONJADRO, 2024)
One of the problems that occur at Madiun Station is the need for modal integration. Modal integration can be interpreted as a complete integration of the types or forms (transport) used to move people and goods from one place (origin) to another (destination). Some problems related to modal integration at Madiun Station are not optimal pedestrian facilities, no clear drop zone point for public transport passengers, and more information instructions regarding connecting transportation. In this study, data collection methods were used by observing the existing conditions of the modal integration facilities in the Sriwijaya Earth Station area. Furthermore, a survey was conducted on LRT passengers at Madiun Station regarding the characteristics of LRT service users and the public's willingness to access modal integration facilities. This study uses the Modal Interaction Matrix and Trip Segment Analysis Method. The results of this study using the Modal Interaction Matrix analysis show that the modal integration facility in the Madiun Station area has an interaction level of -160 or can be categorized as a bad interaction. By providing a proposal for the location of the modal integration facility, it can be seen that the interaction value of the modal integration facility at the Sriwijaya Earth Station has increased to -80 or has a Good category. Furthermore, through calculations using the Trip Segment Analysis method, the greatest time value is for public transport users when they want to access the station or when they want to leave the station. The value of the time needed to access the station for public transport users is 15.3 minutes. And it takes 14.4 minutes for train service users who get off at Madiun Station and want to continue their journey using public transportation.